Neutrophil extracellular traps in health and disease (Swiss Medical Weekly, 2016)
Polymorphonuclear neutrophil granulocytes are the first responders of the immune system to threats by invading microorganisms. In the traditional view, they combat the intruders by phagocytosis and externalisation of granules containing lytic and microbicidal factors. A dozen years ago, this concept was expanded by the observation that neutrophils may react to bacteria by extruding their nuclear chromosomal DNA with attached nuclear and cytoplasmic constituents to form extracellular reticular structures. Since they trapped and immobilised the microbes, they were designated neutrophil extracellular traps (NETs), and their ensuing cell death NETosis. Subsequently, the NETs were shown to act against different types of pathogens, including viruses, and an intricate interplay between the NETs and countermeasures of the pathogens became apparent. The NETs were also found to induce inflammatory responses in the host that contributed to the pathophysiology of autoinflammatory and even autoimmune diseases. Of special interest is the direct link that NETs provide to infections that may initiate and maintain inflammation without the participation of adaptive immunity. In contrast, neutrophils seem capable of activating B cells to produce antibodies relevant to autoimmunity independently of T cell help. Further results imply NETs in the occurrence of thrombosis of the veins and recently also in the generation of arterial plaque. Data from the studies on the defence against pathogens and the pathophysiology of inflammation and thrombosis have started to drive applications to modulate NET formation and its effects and may provide opportunities to optimise current diagnostic and therapeutic concepts.